Rural livelihoods, regional economies and processes of change - Sick, Deborah, 1956- (London: Routledge, 2014)
'For centuries, new technologies and expanding networks of production and consumption have been changing the face of rural economies in significant ways. Millions of rural dwellers have found survival increasingly difficult and have fled to urban centres. Others have remained: some retrenching, struggling to just subsist, others attempting to innovatively redefine their place within'new' rural economies. For the past 30 years, rural economies have largely been ignored by policy makers, but recent growing concerns about food security, environmental degradation, climate change, continued rural poverty, and high rates of out-migration have sparked renewed interest in rural regions. While numerous scholars have examined the changing nature of rural economies and their role in larger national and international development efforts, this collection aims to highlight the iterative processes which shape rural economies by showing how the livelihood strategies of rural dwellers--and by extension the regional economies in which they live--both shape, and are shaped by, larger national and international processes. Presenting case studies from a variety of rural regions around the world, this volume examines the changing face of rural economies. The book argues that regional economies and livelihoods are shaped not just by local conditions, national policies, and global economic forces, but also by the varied responses to changing conditions made by rural residents in any one region.'--
Includes bibliographical references and index.
Keywords: Rural development; Rural population; Rural poor; Technological innovations -- Economic aspects; Regional planning; Manpower policy, Rural